2018
DOI: 10.1097/phm.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effect of Cervical Resistance Training on Head Kinematics in Youth Athletes

Abstract: Greater neck girth and strength may be associated with a lower risk of sport-related concussion due to mitigation of head accelerations by the neck. However, neck strengthening exercise remains unstudied in youth athletes. Therefore, this pilot study assessed the feasibility and effect of targeted neck strengthening exercises in youth athletes. Seventeen participants were allocated to perform 8-wk manual resistance-based neck strengthening (n = 13) or control resistance exercise (n = 4) programs. Before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Cervical-strengthening programs entail minimal risk, and programs as short as 8 weeks have been shown to increase strength and decrease head velocity. 19 However, the influence of cervical strengthening on concussion rates remains inconclusive and could be sport dependent. Previous researchers 13,20 observed that neck strength was not associated with concussion rates in contact sports.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical-strengthening programs entail minimal risk, and programs as short as 8 weeks have been shown to increase strength and decrease head velocity. 19 However, the influence of cervical strengthening on concussion rates remains inconclusive and could be sport dependent. Previous researchers 13,20 observed that neck strength was not associated with concussion rates in contact sports.…”
Section: Discussionmentioning
confidence: 99%
“…is problem is called the inverse kinematics problem. Each joint variable of the robot arm is an independent variable, and the pose of the end effector (hand grip) is usually expressed in the reference coordinate system [28,29]. To determine the corresponding joint variables according to the position and posture of the hand in the reference coordinate system, the inverse kinematics problem needs to be solved [30].…”
Section: Kinematicsmentioning
confidence: 99%
“…A potentially modifiable risk factor in the prevention of fall-related TBI may be neck muscle strength and activation. Resistance training for the neck muscles has been shown to effectively decrease linear head velocity during head loading conditions in young adults [33]. Conversely it has been suggested that dynamic neuromuscular training may provide more benefit for the neck musculature's response to perturbation than resistance training alone [34].…”
Section: Discussionmentioning
confidence: 99%